Long-term motor outcomes of very preterm and/or very low birth weight individuals without cerebral palsy: A review of the current evidence. Issue 3 (June 2020) - Evensen, Kari Anne I.; Ustad, Tordis; Tikanmäki, Marjaana; Haaramo, Peija; Kajantie, Eero
Abstract: We reviewed literature on long-term motor outcomes of individuals aged five years or older born very preterm (VP: ≤32 weeks of gestation) or with very low birth weight (VLBW: ≤1500g), without cerebral palsy (CP). PubMed produced 2827 articles, whereof 38 were eligible. Assessed by standardised and norm-based motor tests, the Movement Assessment Battery for Children being the most widely used, VP/VLBW individuals showed poorer motor skills compared with term-born controls with differences of approximately 1 SD in magnitude. Some studies assessed subdomains and differences were present in fine motor/manual dexterity, ball skills and gross motor/balance. Prevalence of motor problems varied largely from 8-37% in studies with cut-off at the 5th percentile or −1.5 SD to 12–71% in studies with cut-off at the 15th percentile or −1 SD. This review shows that the degree of motor impairments continues to be substantial among VP/VLBW individuals who do not develop CP.